Intracellular Crystal Formation as a Mechanism of Cytotoxicity in Murine Pulmonary Cryptococcus neoformans Infection - Feldmesser, Marta (American Society for Microbiology, 2001)
Rod-like crystalline structures formed during eosinophilic Cryptococcus neoformans pneumonia in C57BL/6 mice. Crystals were found associated with yeast cells and free in host cell cytoplasm. The crystals apparently formed because of the interaction of a host protein with the cryptococcal polysaccharide. Crystal formation likely contributes to pathogenesis by causing cellular damage.